Thermal deformation and stress of alkali-activated slag concrete under semi-adiabatic condition: Experiments and simulations. (September 2022) - Li, Zhenming; Liang, Xuhui; Liu, Chen; Liang, Minfei; van Breugel, Klaas; Ye, Guang
Abstract: This study investigates the deformation of free and stress of restrained alkali-activated slag concrete (AASC), respectively, under semi-adiabatic condition. The concrete shows first thermal expansion, which is compensated soon by autogenous shrinkage. The subsequent cooling down of the concrete aggravates shrinkage and development of tensile stress, which eventually results in early cracking of the concrete. The results show that semi-adiabatic condition is severer for AASC than isothermal condition in view of cracking tendency. The evolutions of coefficient of thermal expansion (CTE) and elastic modulus are measured by elaborated experimental methods. Simulating the deformation of AASC by summing thermal and autogenous deformations appears feasible. With the consideration of relaxation, the stress evolution in restrained AASC can be predicted pretty well by the model used in this paper. This study provides insights into the thermal deformation and cracking tendency of AASC in practical circumstances.